ANALYSIS OF OPTION FOR ENTREPRENEURSHIP OF STUDENTS STUDYING ECONOMICS - Camelia, VECHIU; Gianina, CIORĂȘTEANU (Strategii Manageriale)
Entrepreneurship is important, entrepreneur plays a major role at micro and maroeconomic level. Entrepreneur is the manager and employee at the same time, is leader and innovator, his company provides products and services that society needs. Europe needs more entrepreneurs and those who want to follow the path of entrepreneurship needs to face multiple challenges that can be overcome when the future entrepreneur benefit from a complex entrepreneurship education. This paper aims, through applied questionnaire, to identify whether future economists are determined to choose the path of entrepreneurship and start a business on their own. Also, we wanted to identify the obstacles that interviewees consider that you have to struggle to start their business. We applied a questionnaire to students, final year bachelor's degree, studying economics. They were chosen because during the three years study several economic disciplines: microeconomics, macroeconomics, management, accounting, finance, law, economic analysis, the national economy, European policy.